(untitled) (Ágora Journal, 2021)
This article seeks to explore some possibilities for investigating Independence as a nexus of actions of different generations, and how this generational distinction can be perceived in the action and political discourses of different press agents of the time. We intend to point out age differences as constituent elements of individual trajectories and actions and also as boundary boundaries between them. We will seek to demonstrate the effectiveness of the History of Concepts and the way it deals with historical experiences as a means of identifying generational breaks within the set of our characters. And with the help of the conceptual tools developed by Karl Mannheim, when dealing with the theme of generations, we will give clearer contours to the multigenerational framework of Independence.